2012
DOI: 10.1371/journal.pone.0046239
|View full text |Cite
|
Sign up to set email alerts
|

Ferrous Citrate Up-Regulates the NOS2 through Nuclear Translocation of NFκB Induced by Free Radicals Generation in Mouse Cerebral Endothelial Cells

Abstract: Previous studies indicate that the inducible nitric oxide synthase 2 (NOS2) of the brain vascular tissue in experimental subarachnoid hemorrhage (SAH) rats is a critical factor for inducing cerebral vasospasm. However, the underlying molecular mechanisms remain to be elucidated. Here, we applied ferrous citrate (FC) complexes to the primary cultured mouse cerebral endothelial cell (CEC) to mimic the SAH conditions and to address the issue how SAH-induced NOS2 up-regulation. Using immunocytochemical staining te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
(47 reference statements)
2
13
0
Order By: Relevance
“…The mechanisms underlying the ROS-induced neurotoxicity may involve DNA damage and activation of poly adenosine diphosphate (ADP)-ribose synthase with subsequent depletion of glycerol-3-phosphate dehydrogenase and ATP or mitochondrial damage leading to necrosis and apoptosis. Previously, we demonstrated that FC can increase ROS generation and NOS2 gene expression in mouse CEC [31]. Our data also suggest that increases of ROS might contribute to the FC-induced up-regulation of NOS2 through activation and binding of NFκB onto the NOS2 promoter of the mouse CEC.…”
Section: Discussionsupporting
confidence: 73%
“…The mechanisms underlying the ROS-induced neurotoxicity may involve DNA damage and activation of poly adenosine diphosphate (ADP)-ribose synthase with subsequent depletion of glycerol-3-phosphate dehydrogenase and ATP or mitochondrial damage leading to necrosis and apoptosis. Previously, we demonstrated that FC can increase ROS generation and NOS2 gene expression in mouse CEC [31]. Our data also suggest that increases of ROS might contribute to the FC-induced up-regulation of NOS2 through activation and binding of NFκB onto the NOS2 promoter of the mouse CEC.…”
Section: Discussionsupporting
confidence: 73%
“…Some of the consequences of oxidative stress after SAH include neuroinflammation, disruption of the BBB, and production of spasmogens (Gaetani et al, 1990; Yun et al, 2013). Intracellular ROS activate NF-κB to upregulate NOS 2 (Chen et al, 2012). In addition, ROS can activate apoptotic signals, including p53, caspase-3 and caspase-9 to promote apoptotic cell death (Lu et al, 2013).…”
Section: 3 Neurobiological Response After Sahmentioning
confidence: 99%
“…All the studies implicate the therapeutic potential of citrate for cancer treatment and further comprehensive studies are needed to determine the toxic concentration range to specific cancer types. In addition, it is worthy to note that although citrate has been found to reduce radical surge [185] or alleviate certain cell dysfunction affected by reactive oxygen species (ROS) [155], the existing results are still preliminary and additional research is needed to confirm the antioxidant effect of citrate, since citrate chelating with ferrous ions was also found to elevate intracellular oxidative stress leading to increased ROS production [186, 187]. Therefore, despite its great importance, this aspect of citrate biology is not discussed in the present review.…”
Section: Biology Considerations For Biomaterials Design and Applicationmentioning
confidence: 99%